Bovine leukaemia virus DNA in fresh milk and raw beef for human consumption (2017)
Bovine leukaemia virus (BLV) is the causative agent of enzootic bovine leucosis, which has been reported worldwide. BLV has been found recently in human tissue and it could have a significant impact on human health. A possible hypothesis regarding viral entry to humans is through the consumption of infected foodstuffs. This study was aimed at detecting the presence of BLV DNA in raw beef and fresh milk for human consumption. Nested PCR directed at the BLV gag gene (272 bp) was used as a diagnostic test. PCR products were confirmed by Sanger sequencing. Forty-nine per cent of the samples proved positive for the presence of proviral DNA. This is the first study highlighting the presence of the BLV gag gene in meat products for human consumption and confirms the presence of the viral DNA in raw milk, as in previous reports. The presence of viral DNA in food products could suggest that viral particles may also be found. Further studies are needed to confirm the presence of infected viral particles, even though the present findings could represent a first approach to BLV transmission to humans through foodstuff consumption. Copyright © Cambridge University Press 2017. This is an Open Access article, distributed under the terms of the Creative Commons Attribution licence (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted re-use, distribution, and reproduction in any medium, provided the original work is properly cited.